Quantitative Method as a Tool in Musicological Interdisciplinary Research of Musical Rhetoric - Kowal, Marianna; Woźniak, Monika (Interdisciplinary Studies in Musicology, 2022)
The choice of research method significantly affects the course of research itself. It is becoming increasingly common to see cases of methods from various fields combined to achieve the required results. This is exemplified by the use of a quantitative method in traditional score analysis to verify premises in the field of music psychology. The article addresses the previous views of tradi- tional musicology on the use of natural methods in the field and presents instances of the usefulness of the quantitative method in music research. In the second part, by referring to musical-rhetorical figures, it is shown how this method can deepen the knowledge of both musical-rhetorical figures and have a valuable contribution to the psychology of music.